Preservation method of high-solid-content electrolyte material photocuring 3D printing green body
By adopting the storage method of high-solid electrolyte materials on photocured 3D printed ceramic green box, including surface coating and environmental isolation, the problem of cracks and layering of ceramic green box is easily solved during the storage process, improving its mechanical strength and stability, and increasing the flexibility of 3D printing operations.
Patent Information
- Application Number
- CN202411942398.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-21
AI Technical Summary
The green ceramics produced by photocuring 3D printing are prone to cracks, layering and other problems during storage, which affects the performance of the ceramics. There are many 3D printing parameters and poor flexibility, resulting in unstable green quality.
The storage method of photocuring 3D printed green body is adopted for photocuring of high-solid electrolyte materials. Through physical isolation and optimization of printing parameters, including surface coating of photosensitive resin, secondary curing, environmental isolation and appropriate printing parameter settings, the storage time of green body is extended and the impact of environmental and printing parameters on the performance of electrolyte membrane after sintered is reduced.
It extends the storage time of ceramic green body, improves its mechanical strength and stability, reduces cracking and stratification after sintering, improves the density and ionic conductivity of the electrolyte membrane, and increases the elasticity of 3D printing operations and the integrity of the product.
Smart Images

Figure CN119661236A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of additive manufacturing (3D printing), and in particular relates to a method for preserving a green body of a photocured 3D printed body of a high-solid content electrolyte material. Background Art
[0002] The production of green hydrogen by electrolysis of water with green electricity is the mainstream technology direction for replacing traditional fossil energy with hydrogen energy, which has attracted great attention to the research and development of low-cost, high-efficiency and large-scale SOEC technology. At the same time, SOEC is gradually becoming one of the effective ways to achieve low-cost large-scale production of green hydrogen. In SOEC, the performance of the electrolyte membrane is the key factor that determines the performance of SOEC.
[0003] With the rapid development of product iteration and preparation technology, 3D printing has become a new type of ceramic preparation method that has received much attention in recent years. Among them, photocuring ceramic 3D printing technology has the advantages of high efficiency, low cost, and good precision. It has high versatility in equipment and material requirements and is considered to be one of the most popular and promising 3D printing technologies for manufacturing high-performance ceramics to date. However, the green body produced by photocuring 3D printing cannot be degreased and sintered immediately after printing because the surface needs to be cleaned and dried. Therefore, during this storage process, the ceramic green body is very likely to crack, delaminate, and have other problems due to environmental and storage problems, which ultimately affects the properties of the ceramic itself. At the same time, there are too many parameters involved in photocuring 3D printers, and the operation is very flexible. 3D printed green bodies are also prone to problems due to poor printing parameters.
[0004] The invention patent CN202110492415.5 proposes the preparation and application of a cleaning liquid for 3D printed ceramic blanks. The patent also focuses on the post-processing method of ceramic green blanks, but it is mainly aimed at ultrasonic cleaning and pressure spraying of precise and complex structures. In fact, the structure of conventional electrolyte membrane green blanks is simple and can be cleaned using the same type of acrylate monomers. Whether it is cleaning complex structures or simple structures, the preservation method of the green blanks after cleaning and the conditions and parameters that affect the preservation of ceramic green blanks have not been systematically studied. Summary of the invention
[0005] To solve the above problems, the present invention provides a method for preserving photocurable 3D printed green sheets of high solid content electrolyte materials. The present invention uses a new post-processing preservation technology to preserve 3D printed green sheets from the two aspects of physical isolation and printing parameters, which can extend the storage time of the electrolyte green sheets and reduce the impact of the environment and printing parameters on the performance of the electrolyte membrane after sintering.
[0006] The technical solution is:
[0007] A method for preserving a green body of a photocurable 3D printed body of a high-solid-content electrolyte material, comprising the following steps:
[0008] Step 1: Prepare a green body, and perform DLP photocuring 3D printing on a high-solid content ceramic slurry to prepare a green body of an electrolyte separator;
[0009] Step 2: Surface coating: coating the surface of the green body obtained in step 1 with a photosensitive resin premixed solution or a photosensitive resin monomer with a photoinitiator added thereto;
[0010] Step 3: Secondary curing, maintaining the surface temperature and humidity of the green body and isolating it from the environment;
[0011] Step 4: Degreasing and sintering to obtain the electrolyte membrane.
[0012] In the step 1, the preparation method of the ceramic slurry is: adding ceramic powder, dispersant, defoamer, and photoinitiator to the photosensitive resin premix, mixing evenly, performing vacuum degassing and ball milling, and finally obtaining the ceramic slurry.
[0013] In step 1, the parameters of 3D printing green body are: the illumination intensity of the first layer and single layer is 100mJ / cm 2 ~500mJ / cm 2 , the printing layer thickness is 25μm~100μm, and the disc slurry thickness is 100μm~500μm.
[0014] In the step 1, the 3D printing environment has a temperature of 20° C. to 30° C. and a humidity of 35%.
[0015] In the step 1, the green body of the electrolyte membrane is in the form of one or more of a sheet, a strip, a honeycomb, a corrugated, a threaded or topological structure.
[0016] In the step 1 and / or step 2, the photosensitive resin premix is two or more of 1,6-hexanediol diacrylate (HDDA), hydroxyethyl acrylate (HEA), trimethylolpropane triacrylate (TMPTA), isobornyl methacrylate (IBOMA), tripropylene glycol diacrylate (TPGDA), dipropylene glycol diacrylate (DPGDA), and hydroxyethyl methacrylate (HEMA).
[0017] In the step 2, the photoinitiator added to the photosensitive resin premix is one or more of photoinitiator TPO, photoinitiator 819, photoinitiator 369, photoinitiator 364, and photoinitiator 184; the concentration of the photoinitiator is 0.1wt% to 2.5wt%.
[0018] In the step 2, the photosensitive resin monomer is one of 1,6-hexanediol diacrylate (HDDA), hydroxyethyl acrylate (HEA), trimethylolpropane triacrylate (TMPTA), isobornyl methacrylate (IBOMA), tripropylene glycol diacrylate (TPGDA), dipropylene glycol diacrylate (DPGDA), and hydroxyethyl methacrylate (HEMA).
[0019] In the step 2, the surface coating is carried out at room temperature.
[0020] In step 3, the secondary curing time is 0.1s to 120s, and the light intensity is 40 to 150mJ / cm 2 .
[0021] An electrolyte diaphragm in a water electrolysis device is obtained by the above-mentioned preservation method.
[0022] Beneficial Effects
[0023] 1. The present invention prolongs the storage time of the photocurable 3D printed green body by performing certain post-treatment on the green body. Compared with the untreated green body, the post-treated ceramic green body can be stored away from light for a longer time, and the average mechanical strength of the post-treated ceramic green body is significantly greater than that of the untreated green body, indicating that the interlayer bonding of the protected green body is stronger and tighter.
[0024] 2. The surface of the ceramic green body preserved by resin curing is isolated from the environment, and the system in the cured layer is more uniform and stable. After degreasing and sintering, the cracking and delamination phenomenon of the cured ceramic green body is greatly improved. The density is about 0.5% higher than that of the uncured electrolyte membrane, and the ion conductivity is good, indicating that the surface and internal stability of the preserved electrolyte membrane are good.
[0025] 3. Due to the different precision, parameters and performance of different DLP 3D printers, there will be ceramic green bodies with different printer printing parameters, or ceramic green bodies with different parameters of the same printer. The post-processing preservation of this method is also universal for ceramic green bodies printed with non-optimal parameters, which effectively increases the operational flexibility of light-curing 3D printing preparation and increases the product completeness rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 : Schematic diagram of the DLP light-curing 3D printing process of the present invention.
[0027] Figure 2 : Rheological image of the ceramic slurry of the present invention.
[0028] Figure 3: Ceramic green body without treatment (a), after resin coating (b) and after resin curing (c).
[0029] Figure 4 : Flexural strength images of ceramic green bodies with fixed solid content (50 vol%), different storage times, and coating or not.
[0030] Figure 5 : Flexural strength images of ceramic green bodies with fixed storage time, different solid contents, and coating or not.
[0031] Figure 6 : Thermogravimetric images of ceramic green bodies and the sintering regimes set up.
[0032] Figure 7 : Cross-sectional SEM image of the sintered dense electrolyte membrane.
[0033] Figure 8 : Density and surface roughness of dense electrolyte after sintering.
[0034] Fig. 9 : Pictures of the sintered bodies obtained without post-treatment protection and after post-treatment protection. DETAILED DESCRIPTION
[0035] The following will further, clearly and completely describe the technical solution of the present invention in combination with the embodiments of the present invention. Obviously, due to the influence of various variables that cannot be easily controlled, such as machine parameters and environmental factors, the described embodiments are only part of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The present invention is mainly aimed at the post-processing and storage method of photocuring 3D printing green body. After the ceramic green body is printed and cleaned using the photocuring 3D printing equipment (CeraFab L30, Lithoz, Austria), it needs a certain period of drying and storage before sintering. Therefore, we perform curing and coating storage on the printed ceramic green body to evaluate the impact of the post-processing and storage method on the ceramic green body and the final product. The schematic diagram of the DLP photocuring 3D printing process of the present invention is shown in the figure. Figure 1 At the same time, the present invention also optimizes the dispersant content and solid content of the 3D printing ceramic slurry, and uses model analysis to obtain the optimal solid content. Finally, when the dispersant is 2wt%, a solid content of 50vol% and a viscosity of 10s -1 The rheological image of the ceramic slurry of the present invention is as follows: Figure 2 shown.
[0037] The effect of photosensitive resin coating and preservation on the ceramic green body is judged from the mechanical strength of the ceramic green body. If certain cracks appear in the green body due to volatilization during the preservation process, its mechanical strength will be greatly reduced. The effect of photosensitive resin curing and preservation on the performance of the ceramic film is judged from the performance of the sintered body after degreasing and sintering of the cured or uncured ceramic green body. At the same time, interval tests are carried out based on the optimal printing parameters debugged in the experiment as the standard to judge the effect of post-processing preservation on the operational flexibility of the printing parameters. Untreated ceramic green body, photosensitive resin coated ceramic green body and photosensitive resin cured ceramic green body are shown in Figure 2. Figure 3 shown.
[0038] Example 1 Coating and preservation
[0039] HDDA, HEA, and TPGDA were mixed in a mass ratio of 3:5:2 and mixed with 1.5wt% of a photoinitiator to prepare a resin premix. Ceramic particles were mixed with the resin premix at a volume fraction of 50vol% to prepare a ceramic slurry and perform photocuring 3D printing. The printing parameters were that the light intensity of the first layer and single layer was 100mJ / cm 2 ~500mJ / cm 2 , the printing layer thickness is 25μm~100μm, and the material tray slurry thickness is 100μm~500μm. After printing, the printed ceramic green body is peeled off from the printing platform, cleaned, and then secondary cured, and then coated on its surface with a layer of photosensitive resin premix used to prepare the slurry, that is, a solution obtained by mixing HDDA, HEA, and TPGDA in a mass ratio of 3:5:2. Then seal and store in a dark place for 12h / 24h / 36h, and then test its three-point bending strength.
[0040] Comparative Example 1: Uncoated and stored
[0041] HDDA, HEA, and TPGDA were mixed in a mass ratio of 3:5:2 and mixed with 1.5wt% of a photoinitiator to prepare a resin premix. Ceramic particles were mixed with the resin premix at a volume fraction of 50vol% to prepare a ceramic slurry and perform photocuring 3D printing. The printing parameters were that the light intensity of the first layer and single layer was 100mJ / cm 2 ~500mJ / cm 2 The printing layer thickness is 25μm to 100μm, and the material plate slurry thickness is 100μm to 500μm. After printing, the printed ceramic green body is peeled off from the printing platform, cleaned, and then cured for a second time. Then, it is directly sealed and stored in a dark place for 12h / 24h / 36h before a three-point bending strength test. The bending strength images of the ceramic green body with fixed solid content (50vol%), different storage time, and whether coated or not are shown in the figure. Figure 4As shown in the figure, under different storage times, the mechanical strength of the treated ceramic green body is significantly greater than that of the untreated green body, and a certain stratification trend can also be clearly seen on the surface of the green body.
[0042] Example 2 Curing and preservation
[0043] HDDA, HEA, and TPGDA were mixed in a mass ratio of 3:5:2 and mixed with 1.5wt% of a photoinitiator to prepare a resin premix. Ceramic particles were mixed with the resin premix at a volume fraction of 50vol% to prepare a ceramic slurry and perform photocuring 3D printing. The printing parameters were that the light intensity of the first layer and single layer was 100mJ / cm 2 ~500mJ / cm 2 , the printing layer thickness is 25μm~100μm, and the material tray slurry thickness is 100μm~500μm. After printing is completed, the printed ceramic green body printing platform is peeled off and cleaned, and then a secondary curing is performed, and then a layer of photosensitive resin premix (with photoinitiator added) used to prepare the slurry is coated on its surface, that is, HDDA, HEA, and TPGDA are mixed in a mass ratio of 3:5:2, and mixed with 1.5wt% of photoinitiator to prepare the resin premix. Then an additional photocuring is carried out in the curing box to cure a layer of the resin premix on the surface of the ceramic green body to achieve an isolation effect. Then it is sealed and stored away from light for 12 hours, and sent to a muffle furnace for sintering. After sintering, the density, three-point flexural strength and ionic conductivity are tested. The flexural strength images of ceramic green bodies with fixed storage time, different solid contents, and whether coated or not are as shown in the figure. Figure 5 As shown in the figure, the lower the solid content, the lower the mechanical strength. However, the mechanical strength of the protected green body is significantly greater than that of the untreated green body, and the higher the solid content, the greater the strength difference. Figure 6 According to the exothermic peak of thermogravimetric analysis, an appropriate sintering procedure and holding time were set, and a complete electrolyte membrane was obtained, as shown in Figure 1 shown.
[0044] Comparative Example 2 Uncured Storage
[0045] The printed ceramic green body was peeled off from the printing platform, cleaned, and then directly sealed and stored away from light for 12 hours after secondary curing without resin curing. It was then sent to a muffle furnace for degreasing and sintering, and the density, flexural strength and ionic conductivity of the sintered body were measured.
[0046] Example 3 Controlling Printing Parameters
[0047] Fine-tune the printing parameters based on the originally debugged optimal printing parameters, such as increasing the light intensity of the first layer and single layer, or increasing the printing layer thickness. Carry out a set of comparative experiments when printing is successful to determine whether the post-processing and preservation method of the present invention can correct the sintering defects caused by poor printing parameters. Generally speaking, if the printing parameters are not good, delamination or cracking is likely to occur during the sintering process. This post-processing and preservation method is used to judge the impact of the present invention on the operational flexibility of the printing parameters. Here we use the debugged printing parameters for light-curing 3D printing. The printing parameters are that the light intensity of the first layer and single layer is 100mJ / cm 2 ~500mJ / cm 2 The printing layer thickness is 25μm to 100μm, and the thickness of the material plate slurry is 100μm to 500μm. After printing, the printed green body is not post-processed. After cleaning, it is sealed and kept away from light for 12 hours, and then sent to the muffle furnace for degreasing and sintering, and the performance of the sintered body is tested. The cross-sectional SEM image of the sintered electrolyte is shown in Figure 7 As shown. Figure 7 It can be seen that as the sintering temperature of the electrolyte membrane prepared by the appropriate printing parameters increases, the sample gradually changes from a porous structure to a densified structure. At 1500℃~1600℃, it can be observed that the ceramic particles are well crystallized, tightly arranged, and have no pores on the surface. The density and surface roughness of the dense electrolyte after sintering are shown in Figure 2. Figure 8 As shown in the figure, the density of the sintered electrolyte membrane is above 95%, and the surface roughness is less than 5 μm, which meets the requirements for the density and surface roughness of the electrolyte membrane.
[0048] Comparative Example 3 Adjusting Printing Parameters
[0049] The optimal printing parameters were fine-tuned, and then light-curing 3D printing was performed. The ceramic green body printed with non-optimal parameters was then coated and stored, cured and stored, and then degreased and sintered to examine the relevant parameters. At the same time, the ceramic green body printed with non-optimal parameters was subjected to no post-processing, sealed and light-proof, and then directly sent to a muffle furnace for degreasing and sintering. After sintering, it was found that when the printing parameters were non-optimal, the resulting sintered body would have various undesirable phenomena such as stratification, breakage, and fragility. Fig. 9 As shown in the figure, obvious delamination and damage can be seen. Once cracks or damage occur, the density and ionic conductivity cannot be guaranteed. When the printing parameters are not good, the density and bending strength of the sintered electrolyte membrane are significantly lower than those of the electrolyte membrane prepared with the optimal printing parameters.
Claims
1. A method for preserving a green body of a photocurable 3D printed body of a high solid content electrolyte material, characterized in that: The following steps are involved: Step 1: Prepare a green body, and perform DLP photocuring 3D printing on a high-solid content ceramic slurry to prepare a green body of an electrolyte separator; Step 2: Surface coating: coating the surface of the green body obtained in step 1 with a photosensitive resin premixed solution or a photosensitive resin monomer with a photoinitiator added thereto; Step 3: Secondary curing, maintaining the surface temperature and humidity of the green body and isolating it from the environment; Step 4: Degreasing and sintering to obtain the electrolyte membrane.
2. The method for preserving a high-solid-content electrolyte material photocurable 3D printing green body according to claim 1, characterized in that: In the step 1, the preparation method of the ceramic slurry is: adding ceramic powder, dispersant, defoaming agent, and photoinitiator to the photosensitive resin premix, mixing evenly, vacuum degassing, ball milling, and finally obtaining ceramic slurry; the volume of the ceramic powder is 40-60% of the photosensitive resin premix.
3. The method for preserving a high-solid-content electrolyte material photocurable 3D printing green body according to claim 1, characterized in that: In step 1, the parameters of 3D printing green body are: the illumination intensity of the first layer and single layer is 100mJ / cm 2 ~500mJ / cm 2 , the printing layer thickness is 25μm~100μm, and the disc slurry thickness is 100μm~500μm.
4. The method for preserving a green body of a photocurable 3D printed body of a high solid content electrolyte material according to claim 1, characterized in that: In the step 1, the 3D printing environment has a temperature of 20° C. to 30° C. and a humidity of 35%.
5. The method for preserving a high-solid-content electrolyte material photocurable 3D printing green body according to claim 1, characterized in that: In the step 1, the green body of the electrolyte membrane is in the form of one or more of a sheet, a strip, a honeycomb, a corrugated, a threaded or topological structure.
6. The method for preserving a high-solid electrolyte material photocurable 3D printed green body according to claim 2, characterized in that: In the step 1 and / or step 2, the photosensitive resin premix is two or more of 1,6-hexanediol diacrylate (HDDA), hydroxyethyl acrylate (HEA), trimethylolpropane triacrylate (TMPTA), isobornyl methacrylate (IBOMA), tripropylene glycol diacrylate (TPGDA), dipropylene glycol diacrylate (DPGDA), and hydroxyethyl methacrylate (HEMA).
7. The method for preserving a high-solid-content electrolyte material photocurable 3D printing green body according to claim 1, characterized in that: In the step 2, the photoinitiator added to the photosensitive resin premix is one or more of photoinitiator TPO, photoinitiator 819, photoinitiator 369, photoinitiator 364, and photoinitiator 184; the concentration of the photoinitiator is 0.1wt% to 2.5wt%.
8. The method for preserving a high-solid-content electrolyte material photocurable 3D printing green body according to claim 1, characterized in that: In the step 2, the photosensitive resin monomer is one of 1,6-hexanediol diacrylate (HDDA), hydroxyethyl acrylate (HEA), trimethylolpropane triacrylate (TMPTA), isobornyl methacrylate (IBOMA), tripropylene glycol diacrylate (TPGDA), dipropylene glycol diacrylate (DPGDA), and hydroxyethyl methacrylate (HEMA).
9. The method for preserving a high-solid-content electrolyte material photocurable 3D printing green body according to claim 1, characterized in that: In the step 2, the surface coating is carried out at room temperature; in the step 3, the secondary curing time is 0.1s to 120s, and the light intensity is 40 to 150mJ / cm 2 .
10. An electrolyte membrane in a water electrolysis device, obtained by the preservation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Cleaning solution for high-yield-stress ceramic material 3D printing green body and preparation method and application thereof
CN113234549A